Estimation of a Vintage Capital Model for Electricity Generating - Wills, H. R. (Review of Economic Studies, 1978)
Journal Article Estimation of a Vintage Capital Model for Electricity Generating Get access Hugh R. Wills Hugh R. Wills London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 3, October 1978, Pages 495–510, https://doi.org/10.2307/2297251 Published: 01 October 1978 Article history Received: 01 October 1976 Accepted: 01 July 1977 Published: 01 October 1978